EVALUASI PELAKSANAAN PEMBINAAN EKS NAPITER DALAM MENINGKATKAN KUALITAS HIDUP DAN KEMBALI PRODUKTIF DI MASYARAKAT - Bara, Fransiskus Novaliansen (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT.In the context of law and policy, the rehabilitation program for former terrorists is based on the principles of correctional practice aimed at restoring and rehabilitating offenders so that they can lead productive lives and not repeat their mistakes. This study analyzes the effectiveness of the implementation of the rehabilitation program for former terrorists in improving their quality of life in society and the factors that support and hinder former terrorists from becoming productive again after undergoing rehabilitation. This research utilizes normative research, a process to discover legal rules, legal principles, and legal doctrines to address legal issues. The rehabilitation program for former terrorists in Indonesia plays an important role in improving their quality of life and facilitating their reintegration into society. Through skills training, psychosocial support, and deradicalization programs, many former terrorists have successfully developed economic independence and left extremist ideologies. Supporting and hindering factors play a significant role in determining the success of their reintegration process. Family support, community acceptance, economic assistance, and structured mentoring programs are the main factors that encourage former terrorists to live independently and contribute positively. Keywords: Coaching, Ex-terrorists, Productive.